Pembelajaran Konstruktivisme Dalam Pembelajaran Aqidah Moral Di Sekolah Muhammadiyah Kota Tebing Tinggi - Hasyimi, Ali; Stiadhy , Tho'at; Maulana, Alhafiz; Ningtiaas, Ayu Irma; Nurcahyanti, Ayu (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
This research aims to explore the implementation of Constructivism Theory in teaching Aqidah Akhlak at Muhammadiyah Middle School, Tebing Tinggi City. Through qualitative methods including interviews and documentation review, this research explores how teachers apply Constructivism Theory to improve student engagement and learning outcomes Findings reveal that when teachers apply Constructivism Theory, students become more actively involved in the learning process, resulting in a dynamic and interactive classroom environment The implementation of constructivist theory also faces challenges. Challenges arise when students are apathetic or unresponsive, thus hindering the full realization of the benefits of theory. This study highlights the importance of aligning educational theory with classroom practice in Islamic education and offers insights for improving teaching methods in Islamic schools.